PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS INQUARY LEARNING PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL KELAS IV DI SDN BAMA 2 - Nahdiya Siti Syarah; Damanhuri Damanhuri; A. Syachruroji; Encep Andriana (LPPM Universitas Bina Bangsa, 2023)
Development of student worksheet based on Inquiry Learning on social science subjects Class IV in SDN Bama 2. This study aims to develop student worksheet media based on inquiry learning on social studies subjects, especially the material of togetherness in diversity in Class IV. The research method used by the author, namely research and Development (R&D) research with seven stages: problem analysis, data collection, Product Design, Design Validation, design revision, product trials and final results. To test the feasibility of this student worksheet, an expert validation test is conducted by media experts and material experts. After testing the product with the subject of this study were students of Class IV SDN Bama 2 which amounted to 20 people. Based on the results of validation that learning media worksheet learners based on Inquiry Learning declared